Promoting Lymphangiogenesis and Lymphatic Growth and Remodeling to Treat Cardiovascular and Metabolic Diseases. Issue 1 (1st December 2022) - Liu, Xiaolei; Cui, Kui; Wu, Hao; Li, Kathryn S.; Peng, Qianman; Wang, Donghai; Cowan, Douglas B.; Dixon, J. Brandon; Sathish Srinivasan, R.; Bielenberg, Diane R.; Chen, Kaifu; Wang, Da-Zhi; et al.
Abstract : Lymphatic vessels are low-pressure, blind-ended tubular structures that play a crucial role in the maintenance of tissue fluid homeostasis, immune cell trafficking, and dietary lipid uptake and transport. Emerging research has indicated that the promotion of lymphatic vascular growth, remodeling, and function can reduce inflammation and diminish disease severity in several pathophysiologic conditions. In particular, recent groundbreaking studies have shown that lymphangiogenesis, which describes the formation of new lymphatic vessels from the existing lymphatic vasculature, can be beneficial for the alleviation and resolution of metabolic and cardiovascular diseases. Therefore, promoting lymphangiogenesis represents a promising therapeutic approach. This brief review summarizes the most recent findings related to the modulation of lymphatic function to treat metabolic and cardiovascular diseases such as obesity, myocardial infarction, atherosclerosis, and hypertension. We also discuss experimental and therapeutic approaches to enforce lymphatic growth and remodeling as well as efforts to define the molecular and cellular mechanisms underlying these processes.